Peluang dan Tantangan Pendidikan di Era Society 5.0 - Naufal Rizaldi Gunawan; Anik Nur Handayani (Universitas Ngeri Malang, 2023)
There is always a lesson behind disaster. The era of the Covid-19 pandemic has also accelerated the adoption of tertiary institutions to be able to apply online learning methods with the support of various programs and scholarships. In the future, Indonesia will not only become a digital consumer but must become a player and even a digital producer. With the development of society and the transition towards the Society 5.0 era, the role of parents is increasingly preoccupied with society's needs for increasingly complex individuals. Here, parents need to build a variety of characters to prepare their children to face this period. Selalu ada pelajaran di balik musibah. Munculnya era pandemi Covid-19 juga mempercepat adopsi perguruan tinggi untuk dapat menerapkan metode pembelajaran daring dengan dukungan berbagai program dan beasiswa. Ke depan, Indonesia tidak hanya menjadi konsumen digital tetapi harus menjadi pemain bahkan produsen digital. Dengan adanya perkembangan masyarakat dan transisi mengarah ke era Society 5.0, peran orangtua semakin disibukkan dengan kebutuhan masyarakat akan individu yang semakin kompleks. Di sini, orangtua perlu membangun beragam karakter untuk mempersiapkan anaknya dalam menghadapi masa tersebut.